Análisis de la metodología Building Information Modeling (BIM) para el diseño de sistemas Electrónicos y de Telecomunicaciones en construcciones comerciales para la ciudad de Loja. - Cumbicus Quiroga, Anabela Cecibel (2024)
The present technical report focuses on the application of the Building Information Modeling (BIM) methodology for the design and modeling of electronic and telecommunication systems. It begins with a description of the current state of BIM in Ecuador, comparing it to the traditional Computer-Aided Design (CAD) methodology and emphasizing the importance of adopting BIM in the country's construction industry, despite the lack of a BIM standard in Ecuador at present. The advantages of using BIM are briefly mentioned, and a case study for commercial buildings where this methodology is implemented is presented. During the development of the case study, key terms such as Request for Information (RFI), which are the project requirements from the employer or company, and BIM Execution Plan (BEP), which is the response to the RFI, i.e., how the project will be carried out, are emphasized. Additionally, terms related to modeling such as Levels of Information (LOI), Types of Information (TOI), Integration Strategy, Roles, and BIM Capabilities are utilized, all of which are essential for the proper application of the BIM methodology. Finally, a successful application of this cutting-edge methodology is achieved through the modeling of electronic and telecommunication systems using BIM tools such as AutoCAD, Revit, and Cell BIM, ensuring design quality and allowing for precise quantity estimation, thereby contributing to accurate budgeting for these systems. Based on the case study, a basic Information Delivery Manual (IDM) is proposed, serving as a guide for the application of the BIM methodology in future projects, considering existing international standards and regulations as references for commercial buildings. Keywords: BIM, SDI, Implementation, Systems, Desing, Modeling, Methodology.